Interactive real-time visualization of fault tolerance simulation for induction machines - Muhammad Zin, Nooradzianie; Wan Abdul Munim, Wan Noraishah; Yusof, Yusrina; Mahadan, Mohd Ezwan (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
This research presents a novel graphical user interface (GUI) as a research and teaching tool for analyzing fault tolerance in induction machines (IM) under open-phase faults (OPFs). The study focuses on both three-phase and symmetrical six-phase induction machines, with scenarios involving up to three OPFs. The GUI integrates MATLAB-based simulations, enabling real-time visualization of machine performance under pre-fault and post-fault conditions. For symmetrical six-phase IM, the process begins with obtaining balanced stator currents under healthy conditions. Faulty operations are optimized based on maximum torque (MT) or minimum loss (ML) modes using Excel's "Solver," with results displayed through the GUI. For three-phase IM, the tool simulates and visualizes output waveforms under fault conditions, offering valuable insights into fault tolerance. Maximum torque will be applied as well during faulty. This tool enhances understanding of fault-tolerant control techniques, bridging the gap between theoretical concepts and practical applications. It serves as a teaching aid for students and researchers while also offering a diagnostic tool for industrial applications. Its user-friendly design, combined with the flexibility to adapt to multi-phase machines, positions it as a scalable solution with potential commercialization in both academic and industrial